The Relationship Between Skipping Breakfast and Stress Levels Among Physics Students at Universitas Negeri Makassar - Primadi, Muhamad Baidhowi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Breakfast is an essential part of a healthy diet that contributes to physical and mental health. This study aims to analyze the relationship between the habit of skipping breakfast and stress levels among physics students at Universitas Negeri Makassar. The research employs a quantitative method with a cross-sectional design, involving 20 students selected through purposive sampling. Breakfast frequency data were collected using a questionnaire, while stress levels were measured using the Depression Anxiety Stress Scale-21 (DASS-21). The analysis was conducted using Pearson's correlation test.The results show that the majority of students (65%) skipped breakfast 3-4 times a week, while 20% skipped breakfast every day. Pearson's correlation test revealed a significant negative relationship between breakfast skipping frequency and stress levels (r = -0.60, p < 0.05), indicating that the more frequently breakfast is skipped, the higher the stress levels experienced. These findings highlight the importance of breakfast in maintaining emotional stability and reducing stress, particularly among students facing academic pressures.The conclusion of this study emphasizes the need for regular breakfast habits to support students' mental health. Further research is recommended to explore other factors influencing stress and to increase the sample size to strengthen the generalizability of the findings.